Sociodemographic Factors and Happiness as Determinants of Students' Academic Achievement - Yafi Sabila Rosyad; Dandi Oka Subantara; Salis Miftahul Khoeriyah; Rika Monika; Firmina Theresia Kora (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Students' GPA is frequently linked to a variety of internal and external factors, including sociodemographic characteristics such as gender and area of residence, as well as psychological variables such as happiness levels. However, the association between happiness and academic achievement has not been clearly established in prior study. The purpose of this study is to examine the association between gender, place of residence, and happiness levels in relation to students' Grade Point Average (GPA). The study followed a descriptive correlational strategy. Data was obtained from 62 students using a questionnaire that included factors like gender, place of residence, happiness level, GPA, and the Indonesian version of the Oxford Happiness Questionnaire (OHQI). The research was conducted using the Chi-Square test for categorical correlations, the independent t-test for comparing mean GPAs between groups, and one-way ANOVA to assess the impact of happiness level on GPA. The findings revealed no statistically significant associations were found between gender and happiness level (p=0.481), gender and GPA (p=0.111), place of residence and happiness level (p=0.537), place of residence and GPA (p=0.090), or happiness level and GPA (p=0.401). Nevertheless, students who live with their parents tend to have higher GPAs than students who reside in dorms. The results indicate that no statistically significant associations were observed between gender, place of residence, happiness level, and students’ GPA. Descriptively, students living with their parents tended to have higher GPAs than those residing in dormitories, although this difference was not statistically significant. These findings suggest that sociodemographic characteristics alone may not sufficiently explain variations in academic performance within this sample.